Pengaruh Kualitas Produk, Harga Dan Promosi Terhadap Keputusan Pembelian Barang Di PT ACE Hardware Dumai - Rezeki, Indra; Bangun, Jessica; Naufal, M Dzaky Rafi; Faris, Salman; Nasib, Nasib (Universitas Islam Sumatera Utara, 2024)
This research aims to determine whether product quality, price, and promotion have an influence on purchasing decisions at PT ACE HARDWARE Branch Dumai. The study is conducted among the employees of PT ACE HARDWARE Branch Dumai, with a population of 100 individuals. Due to the limited population size, the sampling technique employed is quota sampling, with a sample size of 100 individuals. Data collection involves both primary data in the form of questionnaires and secondary data obtained through documentation studies. The data analysis technique utilizes quantitative data processed with Smart PLS Version 3.0, involving inner model and outer model testing.The results of this research indicate:1) appositive influence between product quality and purchasing decision variables, 2) a positive impact of price on purchasing decision variables, and 3) a positive effect of promotion on purchasing decision variables